2011
DOI: 10.1097/aln.0b013e318201c42e
|View full text |Cite
|
Sign up to set email alerts
|

Unanticipated Difficult Airway Management in the Prehospital Emergency Setting

Abstract: Background: Difficult intubation management algorithms have proven efficacy in operating rooms but have rarely been assessed in a prehospital emergency setting. We undertook a prospective evaluation of a simple prehospital difficult intubation algorithm. Methods: All of our prehospital emergency physicians and nurse anesthetists were asked to adhere to a simple algorithm in all cases of impossible laryngoscope-assisted tracheal intubation. They received a short refresher course and training in the use of the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(91 citation statements)
references
References 22 publications
4
80
0
7
Order By: Relevance
“…36 More recently, in a retrospective study of 822 emergent intubations, even the enthusiastic team of Sakles et al reported equivalent overall success rates with use of the GVL vs DL (84% vs 86%, respectively). 37 Moreover, other authors have found a very high success rate of airway management by skilled operators outside the OR without 38 or with very infrequent use of VLs. 28,38,39 Despite the rapidly growing use of VLs in the ED and ICU, there is still no evidencebased paradigm where primary airway management outside the OR, particularly endotracheal intubation, relies mainly on video-laryngoscopy.…”
Section: Etiologies Of Airway Complications Outside the Ormentioning
confidence: 99%
“…36 More recently, in a retrospective study of 822 emergent intubations, even the enthusiastic team of Sakles et al reported equivalent overall success rates with use of the GVL vs DL (84% vs 86%, respectively). 37 Moreover, other authors have found a very high success rate of airway management by skilled operators outside the OR without 38 or with very infrequent use of VLs. 28,38,39 Despite the rapidly growing use of VLs in the ED and ICU, there is still no evidencebased paradigm where primary airway management outside the OR, particularly endotracheal intubation, relies mainly on video-laryngoscopy.…”
Section: Etiologies Of Airway Complications Outside the Ormentioning
confidence: 99%
“…Several SADs are now included in these recommendations and in guidelines for out-ofhospital airway management, not only for management of difficult intubation but as a primary approach for those who do not perform tracheal intubation regularly [85][86][87].…”
Section: Intubation Through a Sadmentioning
confidence: 99%
“…In this study, there were also two cases of failed ETI with standard techniques using direct and indirect laryngoscopes, which were salvaged by endoscope-guided ETI through iLMA. Several reports have described the usefulness of ventilation and intubation with iLMA [11][12][13][14], a point emphasized in the ASA-DAM guidelines [1].…”
Section: Discussionmentioning
confidence: 99%